Coating layer of gas sensor, gas sensor and application
The combination of the coating layer of graphite phase C3N4, bimetal molybdate composite material and cyclic macromolecular compound modified graphene oxide is solved, and the problem that gas-sensitive sensors cannot distinguish between hydrogen and toluene is achieved, and high sensitivity detection of hydrogen is achieved and interfering gas removal ensure the accuracy of the detection results.
Patent Information
- Application Number
- CN202411322855.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
Existing gas-sensitive sensors cannot distinguish between hydrogen and toluene, resulting in interference in the detection results and the degree of aging of the insulating oil cannot be accurately judged.
The graphite phase C3N4 and bimetal molybdate composite material are used as the internal material layer, and graphene oxide modified with cyclic macromolecular compound is used as the external material layer to form a coating layer. The outer layer material has a volume screening effect. Only hydrogen is allowed to pass through, eliminating interfering gases.
The sensitivity of the gas-sensitive sensor to hydrogen is improved, the interference to other reducing gases is reduced, and the gas selectivity sensitivity is achieved, ensuring the accuracy of the detection results.
Smart Images

Figure CN119198840A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sensing and measuring technology, and in particular to a coating layer of a gas sensor, a gas sensor and applications. Background Art
[0002] In ultra-high voltage equipment, insulating oil is used in shunt reactors to prevent short circuits. During long-term operation, due to the effects of voltage and temperature, the insulating oil in the shunt reactor will gradually age and crack, resulting in various circuit faults. In order to accurately determine the degree of aging of the insulating oil, its aging products, such as hydrogen, will be detected to determine the degree of aging of the insulating oil. Generally, a gas sensor that detects reducing gas is used to detect the degree of aging of the insulating oil. However, the insulating oil itself is also reducing, and small carbon molecules are also reducing. Its volatilization will interfere with the signal of the gas sensor. In the monitoring of insulating oil deterioration in the power sector, hydrogen can better represent the change of oil products. Traditional gas sensors are sensitive to all reducing gases (including hydrogen and toluene), that is, hydrogen or toluene can produce similar changes in the resistance of the gas sensor. In fact, in the electrical field, hydrogen can characterize the degree of degradation of the insulating oil in the substation equipment, while toluene may come from other places such as the packaging coating of the electrical equipment, which will interfere with the measured target signal and belong to the interference item. Therefore, the existing gas sensors cannot distinguish which factor causes the impact, which will affect the detection results. Summary of the invention
[0003] The purpose of the present invention is to overcome the problem that the existing gas sensors cannot distinguish between hydrogen and toluene, and to provide a coating layer of a gas sensor, a gas sensor and an application. The outer layer of the electrode of the gas sensor is coated with a coating layer. The outer layer material layer of the coating layer has a volume screening effect, which can filter out other interfering gases. Only hydrogen can pass through and be sensed by the gas sensor. The gas sensor of the present invention has high sensitivity to hydrogen and can prevent interference from other reducing gas molecules.
[0004] In order to achieve the above object, the present invention provides a coating layer of a gas sensor, wherein the coating layer comprises an inner material layer and an outer material layer, wherein the outer material layer is coated on the surface of the inner material layer;
[0005] The material of the inner material layer is gC 3 N 4 (where "g" represents graphite phase, gC 3 N 4 That is, the graphite phase C 3 N 4 Material) and a bimetallic molybdate composite material, the gC 3 N 4 and bimetallic molybdate composites by gC 3 N4 It is obtained by sintering with bimetallic molybdate;
[0006] The material of the outer material layer is graphene oxide modified by a cyclic macromolecular compound;
[0007] The cyclic macromolecular compound is cyclodextrin and / or polyurea.
[0008] In the present invention, the bimetallic molybdate has excellent acoustic, photocatalytic, luminescent and sensing properties (wherein the band gap of sodium bismuth molybdate is 2.8eV-3.1eV); gC 3 N 4 The surface nitrogen content is high, which is easy to form -NH or -NH 2 Group, making gC 3 N 4 The surface contains a large number of amino groups as active sites, which are easy to chemically adsorb with reducing gases. 3 N 4 Coupled with semiconductor materials, one is that more target gas molecules can be detected, that is, if the concentration of the monitored target gas is the same, then the gC 3 N 4 It can adsorb more target gases, so that they can be sensed by bimetallic molybdates, which is similar to signal amplification, thus improving sensitivity; secondly, it can also construct a heterojunction, so that the energy band changes, making it easier to react with reducing gases, and also improving gas sensing performance. 3 N 4 Co-sintering with bimetallic molybdates can produce a composite material with better gas sensing properties.
[0009] Further preferably, the gC 3 N 4 The preparation method of the bimetallic molybdate composite material comprises the following steps: 3 N 4 Mix with bimetallic molybdate, then sinter at 400-500℃ for 1-3h;
[0010] Among them, gC 3 N 4 It can be used as an active point to adsorb sensitive gas molecules. The bimetallic molybdate is the main body of the gas-sensitive signal. The two are mixed to form a semiconductor heterojunction, which increases the sensitivity. In order to achieve better results, the gC 3 N 4 The weight ratio to the bimetallic molybdate is preferably 1:3-100.
[0011] More preferably, the bimetallic molybdate is sodium bismuth molybdate and / or potassium bismuth molybdate. In a specific embodiment, the bimetallic molybdate is sodium bismuth molybdate.
[0012] In the present invention, the inner material layer has gas-sensitive detection properties, while the outer material layer has molecular selectivity. In practical applications, the outer material layer will lose a portion of the target water molecules, affecting the molecular selectivity, so the inner material layer is required to have more sensitive gas-sensitive detection properties. Therefore, in order to achieve the corresponding technical effect, the particle size of the bimetallic molybdate is preferably 20-200nm.
[0013] Among them, gC used in the present invention 3 N 4 It can be purchased from a commercial source or can be prepared by self-production. In a specific embodiment, the gC used in the present invention 3 N 4 is obtained by self-production, the gC 3 N 4 The preparation method is the conventional preparation method of gC 3 N 4 The method specifically comprises the following steps: heating urea in a sealed state at 500-600° C. for 1-3 hours.
[0014] In the present invention, the preparation method of the bimetallic molybdate comprises the following steps:
[0015] (1) mixing a bismuth salt solution and a molybdate solution to obtain a suspension, heating the suspension at 150-200° C. (a sodium bismuth molybdate product can be obtained within this temperature range, and the impurity components increase beyond this temperature range, and even sodium bismuth molybdate cannot be formed) for 10-15 hours by a hydrothermal method, and then cooling;
[0016] (2) The material obtained after cooling is subjected to solid-liquid separation, and the solid phase material obtained after the solid-liquid separation is washed and dried.
[0017] In the above preparation method of bimetallic molybdate, if bismuth nitrate, molybdate and solvent are directly mixed together, complexes of different components may be generated. Therefore, it is necessary to prepare bimetallic molybdate by first preparing bismuth nitrate and molybdate into solutions and then mixing them.
[0018] Further in step (1), in order to avoid precipitation of bismuth complex ions, the bismuth salt solution needs to be acidic; therefore, preferably, the bismuth salt is mixed with ethanol, ethylene glycol and nitric acid to obtain a bismuth salt solution; wherein the concentration of the bismuth salt in the bismuth salt solution is 0.5-500 mg / L; the volume ratio of the ethanol, ethylene glycol and nitric acid is 1:0.8-1.1:0.5-5; and the bismuth salt is selected from bismuth nitrate.
[0019] Preferably, in step (1), molybdate is mixed with ethanol, ethylene glycol and water to obtain a molybdate solution; the concentration of molybdate in the molybdate solution is 0.5-500 mg / L; the volume ratio of ethanol, ethylene glycol and water is 1:0.8-1.1:0.5-5; because the bimetallic molybdate finally prepared will not quickly generate other complex ions in the alcohol-water mixture, a solvent similar to that used in the preparation of the bismuth salt solution is used here.
[0020] In the present invention, the molybdate is sodium molybdate and / or potassium molybdate; further in a specific embodiment, the molybdate is sodium molybdate.
[0021] In step (1), in order to further avoid the formation of complexes of other components when the bismuth salt solution and the molybdate solution are mixed, it is preferred that the bismuth salt solution is added dropwise to the sodium molybdate solution while stirring. After the bismuth salt solution is added, stirring is continued for 20-40 minutes until the materials are evenly mixed to obtain a suspension.
[0022] In step (1), the molar ratio of the bismuth salt in the bismuth salt solution to the molybdate in the molybdate solution is 1:2-2.15; when the bismuth ions are excessive, precipitation will occur and sodium bismuth molybdate cannot be formed. Therefore, it is more appropriate to control the molar ratio of the bismuth salt in the bismuth salt solution to the molybdate in the molybdate solution within the above range.
[0023] Further preferably, in step (2), in order to ensure that the material can be fully dried, the drying conditions include: temperature of 60-120° C. and time of 10-15 h.
[0024] In the present invention, graphene oxide modified by cyclic macromolecular compounds is used as the material in the outer material layer to enhance gas selectivity; graphene oxide (GO) is a layered structure with a regular interlayer spacing, and the interlayer spacing can be adjusted by methods such as grafting. Although the interlayer spacing of graphene oxide is much larger than that of hydrogen molecules, part of the hydrogen will still be blocked together with the large volume gas molecules as background noise, thereby reducing the sensitivity of the gas sensor. Therefore, in the present invention, cyclic macromolecular compounds are used to modify graphene oxide and regulate the interlayer spacing of graphene oxide (graphene oxide is a layered structure. After the cyclic macromolecular compound is grafted and modified, the cyclic macromolecules enter the interlayer of graphene oxide, thereby increasing the interlayer spacing), so that large molecular gases cannot penetrate, and only small molecular gases can penetrate and then be detected, so that the gas sensor can have gas selective sensitivity (the gas sensor is exposed to the outside world and will adsorb target gas molecules to obtain electrical signals. When the gas sensor is covered with a layer of graphene oxide grafted with a cyclic macromolecular compound, it is like covering a mosquito net. The interlayer spacing is similar to the small holes in the mosquito net, and molecules with a volume larger than this interlayer spacing are blocked), which is beneficial to improve the overall detection limit of the gas sensor.
[0025] In a specific embodiment, the cyclic macromolecular compound is cyclodextrin.
[0026] The present invention uses graphene oxide modified with cyclic macromolecular compounds because, on the one hand, cyclic macromolecular compounds are easy to graft onto, which hinders the passage of certain gases and makes them selective; on the other hand, the cyclic macromolecular compound itself is a ring structure, and the holes inside the ring allow gas molecules to pass through.
[0027] In the present invention, the selectively permeable gas penetrates through the interlayer spacing of graphene oxide modified by cyclic macromolecular compounds, and interfering gases such as benzene molecules are intercepted due to their large size; the size of the permeable interlayer spacing is mainly determined based on the volume of the interfering gas molecules. In the preferred case of the present invention, the interlayer spacing of the graphene oxide modified by the cyclic macromolecular compound is 0.8-1nm.
[0028] In the present invention, the method for preparing the cyclic macromolecular compound modified graphene oxide comprises the following steps:
[0029] (a) mixing graphene oxide with water to obtain a graphene oxide dispersion, and mixing the graphene oxide dispersion with a cyclic macromolecular compound to obtain a mixed material;
[0030] (b) The mixture is mixed with hydrazine hydrate and aqueous ammonia, and then heated at 50-90° C. (this temperature is easy to react, the reaction is not violent, and it is relatively safe) for 3-5 hours, and then ultrasonically shaken and solid-liquid separated, and the solid phase material obtained after solid-liquid separation is washed and dried.
[0031] Preferably, in step (a), the concentration of graphene oxide in the graphene oxide dispersion is 1-4 mg / mL.
[0032] Further preferably, in step (a), the weight ratio of graphene oxide to cyclic macromolecular compound is 1-5:100 (as a reactant, the cyclic macromolecular compound generally needs to be in excess because only a portion of the cyclic macromolecular compound will react).
[0033] Further, in a specific implementation of step (a), in order to better disperse, after the graphene oxide dispersion is mixed with the cyclic macromolecular compound, a certain amount of water needs to be added, and the amount of water added is only enough to ensure that GO and the cyclic macromolecular compound are completely dispersed (the GO dispersion is GO sheets dispersed in water, and a certain amount of water is added only for dilution to better disperse the reactants).
[0034] In step (b), hydrazine hydrate and ammonia water are used because: hydrazine hydrate can break the molecular chain and increase the reaction rate; ammonia water reacts with the carboxyl group on the graphene oxide, thereby facilitating the smooth grafting of cyclic macromolecular compounds on the graphene oxide.
[0035] Further preferably, in order to achieve better technical effects, the usage ratio of the graphene oxide, hydrazine hydrate and ammonia water is 1 mg: 0.5-3 mL: 0.5-5 mL.
[0036] In step (b), ultrasonic vibration is performed because, on the one hand, it is conducive to the complete reaction. On the other hand, since not all cyclic macromolecular compounds are grafted onto GO, ultrasonic vibration can disperse the unreacted cyclic macromolecular compounds adsorbed on GO into the liquid and then filter them out with the liquid.
[0037] Preferably, in step (b), the drying conditions include: temperature of 50-90° C. and time of 3-5 h.
[0038] A second aspect of the present invention provides a gas sensor, wherein the surface of a ceramic sheet of an interdigital electrode of the gas sensor is coated with the above-mentioned coating layer.
[0039] Furthermore, the method of coating the above coating layer on the surface of the ceramic sheet of the interdigital electrode of the gas sensor includes:
[0040] S1, gC 3 N 4 The bimetallic molybdate composite material is mixed with an organic solvent and ground to obtain gC 3 N 4 and bimetallic molybdate composite paste slurry, gC 3 N 4 and bimetallic molybdate composite material paste slurry are uniformly coated on the outer surface of the ceramic sheet of the interdigital electrode, and dried to form an internal material layer;
[0041] S2. Mix the cyclic macromolecular compound-modified graphene oxide with an organic solvent, grind to obtain a cyclic macromolecular compound-modified graphene oxide paste slurry, evenly apply the cyclic macromolecular compound-modified graphene oxide paste slurry on the outer surface of the inner material layer obtained in step S1, and dry to form an outer material layer.
[0042] In the present invention, if gC is directly coated on the ceramic sheet of the interdigital electrode 3 N 4The bimetallic molybdate composite material and the graphene oxide modified by the cyclic macromolecular compound will fall off easily and cannot form a coating layer. Therefore, the two materials are mixed with volatile organic solvents in advance to obtain a paste slurry for easy coating. The amount of the organic solvent used is sufficient to form a paste slurry after mixing with the material for easy coating. Preferably, the organic solvent used in the present invention is selected from ethanol and / or acetone. In a specific embodiment, the organic solvent used is ethanol.
[0043] In the above gas sensor, the outer material layer acts as a gas selective permeation layer, which selectively permeates only the target gas, while toluene molecules that interfere with the gas are blocked due to their large size and cannot pass through; the inner material layer acts as a gas sensitive material layer, which reacts to the permeated gas and gives a gas sensitive signal. The gas sensor is sensitive to hydrogen, but not toluene, which is also a reducing gas, thus forming a gas selective sensitive effect as a whole.
[0044] A third aspect of the present invention provides an application of the above-mentioned gas sensor in hydrogen detection.
[0045] The present invention sequentially coats gC on the ceramic sheets of the interdigital electrodes of the gas sensor. 3 N 4 An inner material layer is formed by a bimetallic molybdate composite material and an outer material layer is formed by graphene oxide modified by a cyclic macromolecular compound, wherein the graphene oxide sheet modified by the cyclic macromolecular compound and the bimetallic molybdate form a PN structure, which has a certain enhancement effect on the gas-sensitive properties and can give signals under reducing gases at lower concentrations. However, the most important function of the graphene oxide modified by the cyclic macromolecular compound in the outer layer of the present invention is the volume screening effect, which intercepts toluene and other reducing gases, and only hydrogen molecules with smaller volumes can pass through, thereby realizing the selective permeability of the gas sensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 gC prepared in Example 1 3 N 4 and 1wt%-C 3 N 4 XRD spectrum of / NBM composites;
[0047] Figure 2 are XRD spectra of graphene oxide and GO / CD50 and GO / CD100 prepared in Examples 1 and 2;
[0048] Figure 3 It is a schematic diagram of gas sieving of cyclodextrin-modified graphene oxide of the present invention. DETAILED DESCRIPTION
[0049] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific implementation described herein is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0050] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0051] Example 1
[0052] (1) 0.001 mmol of Bi(NO 3 ) 3 ·5H 2 O was dissolved in a mixed solution consisting of 10 mL of anhydrous ethanol, 10 mL of ethylene glycol and 20 mL of dilute nitric acid, and mixed evenly under the action of magnetic stirring to obtain a bismuth nitrate solution (the concentration of bismuth nitrate was 12.1 mg / L); 0.002 mmol of Na 2 MoO 4 ·2H 2 O was dissolved in a mixed solution consisting of 10 mL of anhydrous ethanol, 10 mL of ethylene glycol and 5 mL of deionized water, and mixed evenly under the action of magnetic stirring to obtain a sodium molybdate solution (the concentration of sodium molybdate was 19.4 mg / L;
[0053] (2) adding the bismuth nitrate solution obtained in step (1) dropwise into the sodium molybdate solution (the molar ratio of bismuth nitrate in the bismuth nitrate solution to sodium molybdate in the sodium molybdate solution is 1:2), stirring while dropping, and continuing to stir for 30 minutes after the addition of the bismuth nitrate solution until the materials are evenly mixed to obtain a milky white suspension, transferring the suspension into a polytetrafluoroethylene reactor, heating the suspension at 170° C. for 12 hours by a hydrothermal method, and cooling after the heating is completed;
[0054] (3) Using a circulating water vacuum pump to filter the material obtained after cooling in step (2), washing the solid phase material obtained after the filtration, and then drying the washed material in a constant temperature blast drying oven at 90° C. for 12 h to obtain NaBi(MoO 4 ) 2 (NBM);
[0055] (4) Urea was heated in a sealed container at 550°C for 2 h and then naturally cooled to obtain light yellow gC 3 N 4 ;
[0056] (5) gC obtained in step (4) 3 N 4 The gC was prepared by grinding and mixing with the NBM obtained in step (3) at a weight ratio of 1:99, and then sintering at 450°C for 3h. 3 N 4 and sodium bismuth molybdate composite material (1wt%-C 3 N 4 / NBM composite materials);
[0057] (6) mixing graphene oxide with water to obtain a graphene oxide dispersion having a graphene oxide concentration of 2 mg / mL, taking 1 mL of the graphene oxide dispersion and 50 mg of β-cyclodextrin, placing them in a 50 mL round-bottom flask, adding 20 mL of deionized water, and stirring and dispersing them by ultrasonic vibration to obtain a mixed material;
[0058] (7) Add 1 mL of hydrazine hydrate and 5 mL of ammonia water to the mixture obtained in step (6), respectively, and heat in a water bath at 70° C. with stirring for 4 h after mixing. After heating, ultrasonic vibration is performed for 20 min, and then the solid phase material obtained by filtration is washed using a circulating water vacuum pump. The washed material is then dried in a constant temperature blast drying oven at 60° C. for 3 h to obtain cyclodextrin-modified graphene oxide (GO / CD50);
[0059] (8) 0.5 g of gC obtained in step (5) 3 N 4 The sodium bismuth molybdate composite material was mixed with 5 mL of ethanol and ground to obtain gC 3 N 4 and sodium bismuth molybdate composite material paste slurry, gC 3 N 4 and sodium bismuth molybdate composite material paste slurry is evenly coated on the outer surface of the ceramic sheet of the interdigital electrode, and dried to form an internal material layer;
[0060] (9) 0.1 g of the cyclodextrin-modified graphene oxide obtained in step (7) was mixed with 5 mL of ethanol and ground to obtain a cyclodextrin-modified graphene oxide paste slurry, and the cyclodextrin-modified graphene oxide paste slurry was evenly coated on the outer surface of the inner material layer obtained in step (8), and dried to form an outer material layer to obtain a gas sensor coated with a coating layer (GO-CD50-1wt%-C 3 N 4 / NBM gas sensor).
[0061] Example 2
[0062] (1) 0.001 mmol of Bi(NO 3 )3 ·5H 2 O was dissolved in a mixed solution consisting of 10 mL of anhydrous ethanol, 10 mL of ethylene glycol and 10 mL of dilute nitric acid, and mixed evenly under the action of magnetic stirring to obtain a bismuth nitrate solution (the concentration of bismuth nitrate was 16.2 mg / L); 0.002 mmol of Na 2 MoO 4 ·2H 2 O was dissolved in a mixed solution consisting of 10 mL of anhydrous ethanol, 10 mL of ethylene glycol and 10 mL of deionized water, and mixed evenly under the action of magnetic stirring to obtain a sodium molybdate solution (the concentration of sodium molybdate was 14.8 mg / L);
[0063] (2) adding the bismuth nitrate solution obtained in step (1) dropwise into the sodium molybdate solution (the molar ratio of bismuth nitrate in the bismuth nitrate solution to sodium molybdate in the sodium molybdate solution is 1:2), stirring while dropping, and continuing to stir for 30 minutes after the addition of the bismuth nitrate solution until the materials are evenly mixed to obtain a milky white suspension, transferring the suspension into a polytetrafluoroethylene reactor, heating the suspension at 150° C. for 13 hours by a hydrothermal method, and cooling after the heating is completed;
[0064] (3) Using a circulating water vacuum pump to filter the material obtained after cooling in step (2), washing the solid phase material obtained after the filtration, and then drying the washed material in a constant temperature blast drying oven at 60° C. for 12 h to obtain NaBi(MoO 4 ) 2 (NBM);
[0065] (4) Urea was heated in a sealed container at 550°C for 2 h and then naturally cooled to obtain light yellow gC 3 N 4 ;
[0066] (5) gC obtained in step (4) 3 N 4 The mixture was ground and mixed with the NBM obtained in step (3) at a weight ratio of 2:98, and then sintered at 400°C for 2h to prepare gC 3 N 4 and sodium bismuth molybdate composite material (2wt%-C 3 N 4 / NBM composite materials);
[0067] (6) mixing graphene oxide with water to obtain a graphene oxide dispersion having a graphene oxide concentration of 2 mg / mL, taking 1 mL of the graphene oxide dispersion and 100 mg of β-cyclodextrin, placing them in a 50 mL round-bottom flask, adding 30 mL of deionized water, and stirring and dispersing them by ultrasonic vibration to obtain a mixed material;
[0068] (7) Add 1 mL of hydrazine hydrate and 5 mL of ammonia water to the mixture obtained in step (6), respectively, and heat in a water bath at 70° C. with stirring for 4 h after mixing. After heating, ultrasonic vibration is performed for 20 min, and then the solid phase material obtained by filtration is washed using a circulating water vacuum pump. The washed material is then dried in a constant temperature blast drying oven at 50° C. for 5 h to obtain cyclodextrin-modified graphene oxide (GO / CD100);
[0069] (8) 0.5 g of gC obtained in step (5) 3 N 4 The sodium bismuth molybdate composite material was mixed with 5 mL of ethanol and ground to obtain gC 3 N 4 and sodium bismuth molybdate composite material paste slurry, gC 3 N 4 The composite material paste slurry of sodium bismuth molybdate and bismuth sodium molybdate is uniformly coated on the outer surface of the ceramic sheet of the interdigital electrode, and dried to form an internal material layer to obtain a gas sensor (2wt%-C 3 N 4 / NBM gas sensor);
[0070] (9) 0.1 g of the cyclodextrin-modified graphene oxide obtained in step (7) was mixed with 5 mL of ethanol and ground to obtain a cyclodextrin-modified graphene oxide paste slurry, and the cyclodextrin-modified graphene oxide paste slurry was evenly coated on the outer surface of the inner material layer obtained in step (8), and dried to form an outer material layer to obtain a gas sensor (GO-CD100-2wt%-C 3 N 4 / NBM gas sensor).
[0071] Example 3
[0072] (1) 0.001 mmol of Bi(NO 3 ) 3 ·5H 2 O was dissolved in a mixed solution consisting of 10 mL of anhydrous ethanol, 10 mL of ethylene glycol and 30 mL of dilute nitric acid, and mixed evenly under the action of magnetic stirring to obtain a bismuth nitrate solution (the concentration of bismuth nitrate was 9.9 mg / L); 0.002 mmol of Na 2 MoO 4 ·2H 2 O was dissolved in a mixed solution consisting of 10 mL of anhydrous ethanol, 10 mL of ethylene glycol and 5 mL of deionized water, and mixed evenly under the action of magnetic stirring to obtain a sodium molybdate solution (the concentration of sodium molybdate was 19.4 mg / L);
[0073] (2) adding the bismuth nitrate solution obtained in step (1) dropwise into the sodium molybdate solution (the molar ratio of bismuth nitrate in the bismuth nitrate solution to sodium molybdate in the sodium molybdate solution is 1:2), stirring while dropping, and continuing to stir for 30 minutes after the addition of the bismuth nitrate solution until the materials are evenly mixed to obtain a milky white suspension, transferring the suspension into a polytetrafluoroethylene reactor, heating the suspension at 200° C. for 10 hours by a hydrothermal method, and cooling after the heating is completed;
[0074] (3) Using a circulating water vacuum pump to filter the material obtained after cooling in step (2), washing the solid phase material obtained after the filtration, and then drying the washed material in a constant temperature blast drying oven at 100° C. for 12 h to obtain NaBi(MoO 4 ) 2 (NBM);
[0075] (4) Heat urea at 550°C for 2 h in a sealed container and obtain light yellow gC after natural cooling. 3 N 4 ;
[0076] (5) gC obtained in step (4) 3 N 4 The mixture was ground and mixed with the NBM obtained in step (3) at a weight ratio of 3:97, and then sintered at 500°C for 1 h to prepare gC 3 N 4 and sodium bismuth molybdate composite material (3wt%-C 3 N 4 / NBM composite materials);
[0077] (6) mixing graphene oxide with water to obtain a graphene oxide dispersion having a graphene oxide concentration of 2 mg / mL, taking 2 mL of the graphene oxide dispersion and 100 mg of β-cyclodextrin, placing them in a 50 mL round-bottom flask, adding 30 mL of deionized water, and stirring and dispersing them by ultrasonic vibration to obtain a mixed material;
[0078] (7) Add 8 mL of hydrazine hydrate and 10 mL of ammonia water to the mixture obtained in step (6), respectively, and heat in a water bath at 70° C. with stirring for 4 h after mixing. After heating, ultrasonic vibration is performed for 20 min, and then a circulating water vacuum pump is used for filtration for 1 h. The solid phase material obtained by filtration is washed, and then the washed material is dried in a constant temperature blast drying oven at 50° C. for 5 h to obtain cyclodextrin-modified graphene oxide (GO / CD100);
[0079] (8) 0.5 g of gC obtained in step (5) 3 N 4 The sodium bismuth molybdate composite material was mixed with 6 mL of ethanol and ground to obtain gC3 N 4 and sodium bismuth molybdate composite material paste slurry, gC 3 N 4 and sodium bismuth molybdate composite material paste slurry is evenly coated on the outer surface of the ceramic sheet of the interdigital electrode, and dried to form an internal material layer;
[0080] (9) 0.1 g of the cyclodextrin-modified graphene oxide obtained in step (7) was mixed with 5 mL of ethanol and ground to obtain a cyclodextrin-modified graphene oxide paste slurry, and the cyclodextrin-modified graphene oxide paste slurry was evenly coated on the outer surface of the inner material layer obtained in step (8), and dried to form an outer material layer to obtain a gas sensor (GO-CD100-3wt%-C 3 N 4 / NBM gas sensor).
[0081] Comparative Example 1
[0082] The method of Example 1 is used, except that only gC is uniformly coated on the outer surface of the ceramic sheet of the interdigital electrode. 3 N 4 and sodium bismuth molybdate composite material paste slurry, drying to form an internal material layer, without further coating cyclodextrin-modified graphene oxide paste slurry, that is, a gas sensor (1wt%-C 3 N 4 / NBM gas sensor).
[0083] Comparative Example 2
[0084] The method of Example 2 is used, except that only gC is uniformly coated on the outer surface of the ceramic sheet of the interdigital electrode. 3 N 4 and sodium bismuth molybdate composite material paste slurry, drying to form an internal material layer, without further coating cyclodextrin-modified graphene oxide paste slurry, that is, a gas sensor (2wt%-C) coated only with the internal material layer is obtained. 3 N 4 / NBM gas sensor).
[0085] Comparative Example 3
[0086] The method of Example 1 was followed, except that the outer surface of the ceramic sheet of the interdigitated electrode was directly and evenly coated with a cyclodextrin-modified graphene oxide paste slurry without coating gC 3 N 4 and sodium bismuth molybdate composite material paste slurry, and drying to form an inner material layer, that is, a gas sensor (GO-CD50 gas sensor) coated with only an outer material layer is obtained.
[0087] Comparative Example 4
[0088] The method of Example 2 was followed, except that the cyclodextrin-modified graphene oxide paste was directly and evenly coated on the outer surface of the ceramic sheet of the interdigital electrode without coating gC 3 N 4 and sodium bismuth molybdate composite material paste slurry, and drying to form an inner material layer, that is, a gas sensor (GO-CD100 gas sensor) coated with only an outer material layer is obtained.
[0089] Test Example 1
[0090] The gC prepared in Example 1 3 N 4 and 1wt%-C 3 N 4 The / NBM composite material was subjected to XRD testing, and the XRD spectrum was shown in Figure 1 As shown, by 3 N 4 The standard card (JCPDS NO.87-1526) and the sodium bismuth molybdate XRD standard card (JCPDS NO.88-0242) are available. The gC prepared in this example 3 N 4 The sample shows that it is indeed a graphite phase, and 1wt%-C 3 N 4 The XRD diffraction peaks in the / NBM composite material also correspond to the sodium bismuth molybdate standard card, proving that 1wt%-C 3 N 4 / NBM composite material contains sodium bismuth molybdate.
[0091] Test Example 2
[0092] XRD detection was performed on the graphene oxide used in the examples and the cyclodextrin-modified graphene oxide prepared in Examples 1-3, wherein the XRD spectra of the graphene oxide and the cyclodextrin-modified graphene oxide prepared in Examples 1 and 2 are as follows: Figure 2 As shown, according to Figure 2 It can be seen that the interlayer spacing of GO corresponds to 0.83nm, the interlayer spacing of GO / CD50 prepared in Example 1 is 0.87nm, the interlayer spacing of GO / CD100 prepared in Example 2 is 0.93nm, and the interlayer spacing of GO / CD100 prepared in Example 3 is 0.90nm. It can be seen that the interlayer spacing of graphene oxide becomes larger after modification with cyclodextrin, and with the increase of cyclodextrin content, the diffraction peak shifts to the left, indicating that the interlayer spacing of graphene oxide becomes larger.
[0093] Test Example 3
[0094] The gas sensors obtained in Examples 1-3 and Comparative Examples 1-4 were contacted with 100 ppm hydrogen and 100 ppm toluene gas, respectively, and the response values, response times and recovery times of the gas sensors obtained in Examples 1-3 and Comparative Examples 1-4 to 100 ppm hydrogen and 100 ppm toluene gas were tested, respectively, as shown in Table 1;
[0095] The response value is calculated using the calculation formula of the n-type semiconductor gas sensor: S = Rg / Ra, S is the response value, Rg is the resistance value of the gas sensor in the air, and Ra is the resistance value of the gas sensor in the gas to be tested;
[0096] The response time (tres.) and recovery time (trec.) are the time taken for the resistance value of the gas sensor to reach 90% of the steady state from contact / leave with the gas.
[0097] Table 1
[0098]
[0099] As can be seen from the above table, the present invention adds a coating layer to the gas sensor, and uses cyclodextrin-modified graphene oxide as a material to prepare a gas selective permeation layer. The screening mechanism of the gas selective permeation layer is as follows: Figure 3 As shown, Figure 3 In the figure, green is grafted cyclodextrin, the plane is graphene oxide sheet, the blue ball is hydrogen, and the yellow is toluene molecule that interferes with the signal. Since the volume of toluene molecules is larger than the gap between modified GO sheets, and hydrogen molecules are smaller than the gap between modified GO sheets, hydrogen molecules can pass through the selection layer, while toluene molecules are intercepted; the gas sensors in Examples 1-3 only respond to hydrogen, while Comparative Examples 1-2 respond to both hydrogen and toluene, and Comparative Examples 3-4 have no response to both hydrogen and toluene, indicating that the outer selection layer of the gas sensor in the embodiment of the present invention can pass hydrogen and intercept toluene, while the inner layer has a better response effect to hydrogen. It can be seen that the gas sensor of the present invention is selective, insensitive to the interfering gas toluene, and only sensitive to the target gas hydrogen.
[0100] It should be understood that parts not elaborated in detail in this specification belong to the prior art.
[0101] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A coating layer of a gas sensor, characterized in that: The coating layer comprises an inner material layer and an outer material layer, wherein the outer material layer is coated on the surface of the inner material layer; The material of the inner material layer is a composite material of g-C3N4 and bimetallic molybdate, and the composite material of g-C3N4 and bimetallic molybdate is obtained by sintering g-C3N4 and bimetallic molybdate; The material of the outer material layer is graphene oxide modified by a cyclic macromolecular compound; The cyclic macromolecular compound is cyclodextrin and / or polyurea.
2. The coating layer according to claim 1, characterized in that The preparation method of the g-C3N4 and bimetallic molybdate composite material comprises the following steps: mixing g-C3N4 with bimetallic molybdate, and then sintering at 400-500° C. for 1-3 hours; The weight ratio of the g-C3N4 to the bimetallic molybdate is 1:3-100.
3. The coating layer according to claim 1 or 2, characterized in that: The bimetallic molybdate is sodium bismuth molybdate and / or potassium bismuth molybdate; The particle size of the bimetallic molybdate is 20-200 nm.
4. The coating layer according to claim 2, characterized in that The preparation method of g-C3N4 comprises the following steps: heating urea at 500-600°C for 1-3h in a sealed container.
5. The coating layer according to claim 2, characterized in that: The preparation method of the bimetallic molybdate comprises the following steps: Mixing a bismuth salt solution and a molybdate solution to obtain a suspension, heating the suspension at 150-200° C. for 10-15 hours by a hydrothermal method, and then cooling; The material obtained after cooling is subjected to solid-liquid separation, and the solid phase material obtained after the solid-liquid separation is washed and dried.
6. The coating layer according to claim 5, characterized in that The bismuth salt is mixed with ethanol, ethylene glycol and nitric acid to obtain a bismuth salt solution; The concentration of bismuth salt in the bismuth salt solution is 0.5-500 mg / L; the volume ratio of ethanol, ethylene glycol and nitric acid is 1:0.8-1.1:0.5-5; The bismuth salt is selected from bismuth nitrate.
7. The coating layer according to claim 5 or 6, characterized in that: After mixing molybdate with ethanol, ethylene glycol and water, a molybdate solution is obtained; The concentration of molybdate in the molybdate solution is 0.5-500 mg / L; the volume ratio of ethanol, ethylene glycol and water is 1:0.8-1.1:0.5-5; The molybdate is sodium molybdate and / or potassium molybdate.
8. The coating layer according to claim 5 or 6, characterized in that: The molar ratio of the bismuth salt in the bismuth salt solution to the molybdate in the molybdate solution is 1:2-2.
15.
9. The coating layer according to claim 5, characterized in that: The drying conditions include: temperature of 60-120° C. and time of 10-15 h.
10. The coating layer according to claim 1, characterized in that The interlayer distance of the graphene oxide modified by the cyclic macromolecular compound is 0.8-1 nm.
11. The coating layer according to claim 1 or 10, characterized in that: The preparation method of the cyclic macromolecular compound modified graphene oxide comprises the following steps: Mixing graphene oxide with water to obtain a graphene oxide dispersion, and mixing the graphene oxide dispersion with a cyclic macromolecular compound to obtain a mixed material; The mixed material is mixed with hydrazine hydrate and ammonia water, and then heated at 50-90° C. for 3-5 hours, and then ultrasonically shaken and solid-liquid separated, and the solid phase material obtained after solid-liquid separation is washed and dried.
12. The coating layer according to claim 11, characterized in that The concentration of graphene oxide in the graphene oxide dispersion is 1-4 mg / mL; The weight ratio of the graphene oxide to the cyclic macromolecular compound is 1-5:
100.
13. The coating layer according to claim 11, characterized in that The usage ratio of graphene oxide, hydrazine hydrate and ammonia water is 1 mg: 0.5-3 mL: 0.5-5 mL; The drying conditions include: temperature of 50-90° C. and time of 3-5 hours.
14. A gas sensor, characterized in that: The surface of the ceramic sheet of the interdigital electrode of the gas sensor is coated with the coating layer according to any one of claims 1 to 13.
15. Use of the gas sensor according to claim 14 in hydrogen detection.
